The Utility of Virtual Reality Simulation in Cataract Surgery Training: A Systematic Review - Winebrake, James P.; McMahon, Jeffrey F.; Sun, Grace (Journal of Academic Ophthalmology, 2020)
Introduction Cataract surgery is a fundamental intraocular procedure with a steep learning curve. Virtual reality simulation offers opportunity to streamline this aspect of ophthalmic education by exposing trainees to operative techniques in a controlled setting.Materials and Methods A systematic review of the PubMed database was conducted through December 2019 for English language studies reporting on use of virtual reality simulation in cataract surgery training to assess usefulness. Studies meeting inclusion criteria were examined for pertinent data: study design, number of subjects and live cases, simulator model, training regimen, surgical skills assessed, and overall outcomes.Results Of the 41 analyzed studies, 15 investigated the impact of virtual reality simulation-based training on performance in live surgery or wet laboratories; 20 used simulation as a device for direct assessment of operative proficiency; 6 explored simulation-based training's effect on performance in simulated surgery. Thirty-seven studies employed an iteration of the Eyesi simulator, though methodologies varied widely with a few randomized trials available. The literature endorsed validity of simulator-based assessment and benefits of structured training on live complication rates, operative times, and self- and faculty-perceived competency, particularly in novice surgeons.Discussion The literature surrounding simulation in cataract surgery training is characterized by significant heterogeneity in design. However, most works describe advantages that may outweigh the costs of implementation into training curricula. Collaborative efforts at establishing a structured, proficiency-based cataract surgery curriculum built around virtual reality and wet laboratory simulation have the potential to improve outcomes and enhance future surgical training.
Keywords: simulator; simulation-based training; virtual reality simulation; cataract surgery; Eyesi; residency training; education; systematic review